Congenital double cervix abnormality in a heifer - Mustafa Sönmez; Murat Yüksel (Eurasian Journal of Veterinary Sciences)
In this report, a case of double cervix which is congenital anotomical defect of the female reproductive tract was described in a Brown Swiss heifer. The caudal portion of cervical canal bifurcated although ovarium, oviduct, comu uteri and corpus uteri were normal. This condition is very seldom and attribute to failure of fusion of the caudal portions of pa-ramesonepric (Muellerian) ducts during embrionic development.